Facing Demographic Challenges: Pension Cuts or Tax Hikes? - Kudrna, George; Tran, Chung; Woodland, Alan (My University, 2017)
A challenge that faces many advanced economies is how to finance age-related spending programs as the population ages. In this paper, we investigate two policy options - pension cuts and tax hikes - to mitigate fiscal pressure arising in the special context of Australia, whose population is ageing fast while growing substantially in size due to immigration. Using a computable overlapping generations model, we find that while both policy reforms can achieve a similar fiscal goal, they lead to different distributional and welfare effects across income groups over time. Future generations prefer pension cuts, whereas current generations prefer tax hikes to finance government spending commitments. Moreover, within the tax hike option taxing income or consumption results in opposing macroeconomic and welfare effects. Indeed, our opposing intra- and inter-temporal welfare outcomes highlight some political complexity when devising a more sustainable tax-transfer system.
Keywords: Finance; Income, wealth and finances; Finance; Income, wealth and finance